Optimization of Patrols by the Samapta Unit to Prevent Theft Crimes with The Ballast under the Law of The Pekalongan Polres - Arif Rahmansyah (Advances in Police Science Research Journal, 2022)
One of the main tasks of the Samapta Unit is conducting Turjawali. Turjawali is one of the preventive efforts of the police agency to prevent the occurrence of a disturbance threshold. Patrol is one of the police activities to prevent crime as regulated in Perkabaharkam Polri Number 1 of 2017. Based on the background of the high number of cases of theft with severity compared to other crimes that occur in the jurisdiction of the Pekalongan Police, the Police need to carry out Patrol Actions to prevent intentions and opportunities for criminals, especially in the report. This final project was prepared using a qualitative approach and using field research. Sources of data include primary data sources and secondary data with data collection techniques used are interviews, observations, and document studies. In this study, POAC management theory, crime prevention theory and patrol concepts are used in accordance with Polri Perkabaharkam Number 1 of 2017. The results of this study found that the crime of stealing to date is the highest crime that occurs in the jurisdiction of the Pekalongan Police. The patrols carried out by the Pekalongan Police Samapta unit have been carried out in accordance with the preparation, implementation, and termination procedures. However, there are factors that affect the patrol so that it becomes less than optimal, starting from the limitations of members and the extent of the jurisdiction of the Pekalongan Police and the lack of participation from the community. Based on the results of the study, the authors suggest that in carrying out patrol activities involve dalmas members who are not on duty, propose Sat Samapta members to carry out vocational education and collaborate with the surrounding community such as security posts, security posts and hansip posts to monitor locations that are prone to incidents criminal act.